Avaliação da atenuação da luz laser vermelha no tecido gengival em pacientes com pigmentação melânica e doença periodontal – estudo clínico - Arruda, Regina Teresa Fruet (2019)
Photodynamic antimicrobial chemotherapy (PACT) is used as adjunctive treatment for periodontitis and the presence of melanic pigmentation may interfere with absorption and scattering of the therapeutic dose light. The objective of this clinical study was to measure the red light attenuation ʎ = 660 nm in gingival tissue naturally pigmented with melanin. A laser with output power of 100 mW (Photon Lase III, DMC, São Carlos, Brazil) was used. Images were collected with T2i camera (Canon, Japan) with 100 mm macro lens, 35 mm focal focal length, aperture f22, 1/100 shutter speed and ISO 200. The patients were photographed in frontal and incisal regions. This clinical trial included 10 patients with melanin pigmentation in the gingival tissue and were under periodontal treatment at the UNINOVE dentistry clinic. Three sites of each patient were selected for evaluations and a frontal and an incisal site of each patient was randomly selected. The images were evaluated in the IMAGEJ software (NIH, Wayne Rasband, USA) and the intensity in pixels was quantified in relation to the distance from the light incident point. The data were normalized and the results were presented as relative light intensity as a function of distance. The results demonstrated that red laser light is exponentially attenuated as a function of lateral distance and loses approximately 50% of its intensity by 2.23 mm. On the other hand, the light travels 3 mm in depth to decay 50%. In conclusion, our data suggest that irradiation protocols for antimicrobial photodynamic therapy in gingival tissue should take into account the light attenuation and depth of the treated pockets so that efficient illumination of the target tissue occurs.